Harmonization of Customary Law and Islamic Law in the Management of Forbidden Lakes in Village Communities - Zulfahmi (Journal of Social Studies and Education, 2025)
This study examines the harmonization between customary law and Islamic law in managing the Lubuk Larangan tradition in the Tambangan District, Mandailing Natal community. The main focus of the study is to analyze the application of customary sanctions against violations of the Lubuk Larangan rules from the perspective of Islamic criminal law, to spread the harmony of this tradition with the values ​​of maqashid al-syariah, and to explore its contribution to creating harmony between customary norms and Islamic law. This study uses a qualitative approach with a case study design involving seven villages, namely Tambangan Tonga, Tambangan Jae, Rao-Rao Lombang, Rao-Rao Dolok, Tambangan Pasoman, Laru Lombang, and Lumban Pasir. Data were obtained through interviews with customary leaders (hatobangon), religious leaders, and village officials, as well as participatory observation of the implementation of the tradition. The study results indicate that the lubuk larangan tradition functions as a local mechanism in sustainable natural resource management and reflects the application of the principle of hifz al-bi'ah in maqashid al-syariah. Customary sanctions in the form of varying fines have been proven to align with the ta'zir principle in Islamic criminal law, which emphasizes the deterrent effect and restorative justice. This lubuk larangan tradition contributes to maintaining social harmony through combining local wisdom and Islamic values. It is an effective means of preserving the environment while strengthening the cultural identity of the local community.